Modeling’s Effect of Irregular Building Structure with Vegetated Roof on Seismic Evaluation per ASCE 41-17 - Fathurrachman, Muhammad Puja; Satyarno, Iman; Sulistyo, Djoko (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the seismic vulnerability of an irregular educational building with a vegetated roof in Yogyakarta using linear procedures based on ASCE 41-17. Modelling approaches differ Model 1 treats skylights and planter boxes as loads with straight roof slabs, while Models 2 and 3 use shells with sloping roof slabs. Vegetated roofs are featured in Models 1 and 2. The analysis, conducted at seismic hazard levels BSE-1N and BSE-2N using the ETABS program, evaluates structural components and compares Response Spectrum (RS) and Linear Time History (LTH) methods. Results show seismic weight variations of 1.20% to 15.04% between models. Model 1 fails to meet the criteria for modal analysis, while Models 2 and 3 do. The structural performance evaluation based on average demands at BSE-1N and BSE-2N levels varied from Immediate Occupancy to Life Safety performance. The LTH method in all models had higher acceptance ratios than the RS method.